Hadith #2765 - Sahih al-Bukhari - Tha'laba bin Abi Malik (Sahih al-Bukhari)
`Umar bin Al-Khattab distributed some garments amongst the women of Medina. One good garment remained, and one of those present with him said, “O chief of the believers! Give this garment to your wife, the (grand) daughter of Allah’s Messenger (ﷺ).” They meant Um Kulthum, the daughter of `Ali. `Umar said, Um Salit has more right (to have it).” Um Salit was amongst those Ansari women who had given the pledge of allegiance to Allah’s Messenger (ﷺ).’ `Umar said, “She (i.e. Um Sali
Grade: Sahih

Hadith #2852 - Sahih al-Bukhari - Tha'laba bin Abi Malik (Sahih al-Bukhari)
When Qais bin Sa`d Al-Ansari, who used to carry the flag of the Prophet, intended to perform Hajj, he combed his hair.
Grade: Sahih

Hadith #3900 - Sahih al-Bukhari - Tha'laba bin Abi Malik (Sahih al-Bukhari)
`Umar bin Al-Khattab distributed woolen clothes amongst some women of Medina, and a nice woolen garment remained. Some of those who were sitting with him, said, “O chief of the believers! Give it to the daughter of Allah’s Messenger (ﷺ) who is with you,” and by that, they meant Um Kulthum, the daughter of `Ali. `Umar said, “Um Salit has got more right than she.” Um Salit was amongst those Ansari women who had given the pledge of allegiance to Allah’s Messenger (ﷺ) . `Umar added,
Grade: Sahih